2011
DOI: 10.1063/1.3556950
|View full text |Cite
|
Sign up to set email alerts
|

Selol-loaded magnetic nanocapsules: A new approach for hyperthermia cancer therapy

Abstract: Polylactic-co-glycolic nanocapsules, loaded with nanosized magnetic particles and Selol (a selenium-based anticancer drug), were successfully prepared by the precipitation method. Maghemite (γ-Fe2O3) nanoparticles were incorporated into the nanocapsules using a highly stable ionic magnetic fluid sample. The obtained nanocapsules presented no agglomeration, negative surface charge while revealing a narrow monomodal size distribution. All the nanocapsule formulations exhibited a good physical stability at 4 °C d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…17 The polymeric nanocapsules were prepared according to a modified precipitation method previously described. 16 Briefly, PLGA 50:50 polymer (Sigma-Aldrich Co, St Louis, MO), selol 5%, and phosphatidylcholine (Gerbras, Anápolis, Brazil) were dissolved in acetone (JT Baker, Phillipsburg, NJ) at 40°C. This organic phase was added into an aqueous phase containing the poloxamer 188 (Sigma-Aldrich Co) and the ionic magnetic fluid sample (added into the preparation of magnetic nanocapsules).…”
Section: Materials and Methods Nanocapsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The polymeric nanocapsules were prepared according to a modified precipitation method previously described. 16 Briefly, PLGA 50:50 polymer (Sigma-Aldrich Co, St Louis, MO), selol 5%, and phosphatidylcholine (Gerbras, Anápolis, Brazil) were dissolved in acetone (JT Baker, Phillipsburg, NJ) at 40°C. This organic phase was added into an aqueous phase containing the poloxamer 188 (Sigma-Aldrich Co) and the ionic magnetic fluid sample (added into the preparation of magnetic nanocapsules).…”
Section: Materials and Methods Nanocapsulesmentioning
confidence: 99%
“…Moreover, magnetohyperthermia can also be used as an adjuvant therapy to conventional cancer treatments by improving the efficacy of chemotherapy and radiotherapy. 2 A PLGA-MDDS formulation co-encapsulating maghemite nanoparticles and selol (MSE-NC) was recently developed, 16 aiming to provide a new antitumor therapy. Selol is a mixture of selenitetriglycerides synthesized from sunflower oil, containing selenium (+4) in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Here, these materials were adopted to construct the PEGylated poly(diselenide-phosphate) nanogel through the 'arm first' procedure. [47][48][49] Here, these materials were adopted to construct the PEGylated poly(diselenide-phosphate) nanogel through the 'arm first' procedure.…”
Section: Preparation Of the Pegylated Poly(diselenide-phosphate) Nanogelmentioning
confidence: 99%
“…cDDP-containing nanoparticles were found to be more cytotoxic in resistant and native A2780 cells. Other studies have also reported the release of cisplatin from magnetic nanoparticles [140,141] and other drugs, including bleomycin [142], concanavalin A [142], cyclophosphamide [143] and gemcitabine [144]. …”
Section: Clinical Aspects Of Thermal Potentiation Of Chemotherapeuticmentioning
confidence: 99%